Wpływ paranoi politycznej na dyskurs publiczny w Polsce - Jakubowski, Jakub (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The transition of the Polish political system has had a significant influence on the shape of public discourse. Undoubtedly, politicians’ and society members’ disposition to paranoid behaviour is the reason of public debate`s exacerbation and deep conflict between conservatives and liberals. The abundance of political changes, breakthrough circumstances and crisis situations in the last few years have fuelled this trend. In fact, the influence of political paranoia on Polish discourse seems to be destabilised and it provokes a question: how to make debate more substantive and rational?